Analysis of bias induced by various forward projection models in iterative reconstruction - Schmitt, Katharina; Schöndube, Harald; Stierstorfer, Karl; Hornegger, Joachim; Noo, Frédéric (Proceedings of the second international conference on image formation in x-ray computed tomography, 2012)

Challenges posed by statistical weights and data redundancies in iterative X-ray CT reconstruction - Schmitt, Katharina; Schöndube, Harald; Stiersdorfer, Karl; Hornegger, Joachim; Noo, Frédéric (Proceedings of the 12th Fully Three-Dimensional image Reconstruction in Radiology and Nuclear Medicine, 2013)

Comparative evaluation of linear interpolation models for iterative reconstruction in X-ray CT - Schmitt, Katharina; Schöndube, Harald; Stiersdorfer, Karl; Hornegger, Joachim; Noo, Frédéric (Medical Imaging 2013: Physics of Medical Imaging, 2013)
The forward projection operator is a key component of every iterative reconstruction method in X-ray computed tomography (CT). Besides the choices being made in the definition of the objective function and associated constraints, the forward projection model affects both bias and noise properties of the reconstruction. In this work, we compare three important forward projection models that rely on linear interpolation: the Joseph method, the distance-driven method, and the image representation using B-splines of order n = 1. The comparison focuses on bias and noise in the image as a function of the resolution. X-ray CT data that are simulated in fan-beam geometry with two different magnification factors are used. © 2013 SPIE.

Iterative reconstruction using a pyramid-shaped basis function - Schmitt, Katharina; Noo, Frédéric; Hornegger, Joachim; Stierstorfer, Karl; Schöndube, Harald (2012 IEEE Nuclear Science Symposium and Medical Imaging Conference Record (NSS/MIC), 2012)